2004
DOI: 10.1074/jbc.m409079200
|View full text |Cite
|
Sign up to set email alerts
|

Atf1-Pcr1-M26 Complex Links Stress-activated MAPK and cAMP-dependent Protein Kinase Pathways via Chromatin Remodeling of cgs2+

Abstract: Although co-ordinate interaction between different signal transduction pathways is essential for developmental decisions, interpathway connections are often obscured and difficult to identify due to cross-talk. Here signals from the fission yeast stress-activated MAPK Spc1 are shown to regulate Cgs2, a negative regulator of the cAMP-dependent protein kinase (protein kinase A) pathway. Pathway integration is achieved via Spc1-dependent binding of Atf1-Pcr1 heterodimer to an M26 DNA site in the cgs2 ؉ promoter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 49 publications
2
67
0
Order By: Relevance
“…It has also been reported that the Atf1/Pcr1 heterodimer functions as both an inducer and a repressor of chromatin remodeling at the cgs2 promoter (9). According to our data, Atf1 and Pcr1 down-regulate the basal transcription of 4% and 6% of the whole S. pombe genome, respectively.…”
mentioning
confidence: 51%
“…It has also been reported that the Atf1/Pcr1 heterodimer functions as both an inducer and a repressor of chromatin remodeling at the cgs2 promoter (9). According to our data, Atf1 and Pcr1 down-regulate the basal transcription of 4% and 6% of the whole S. pombe genome, respectively.…”
mentioning
confidence: 51%
“…We previously reported that the Atf1-Pcr1-M26 complex links stress-activated mitogen-activated protein kinase and protein kinase A signaling pathways via chromatin remodeling in the cgs2 ϩ promoter (3). In that case, we suggested that the chromatin remodeling facilitates transcriptional activation of cgs2 ϩ (3).…”
Section: Vol 6 2007 Chromatin Configuration At Meiotic Dsb Sites Inmentioning
confidence: 86%
“…A similar mechanism might operate in the control of ste11 expression in response to nitrogen starvation. Furthermore, it is noteworthy that the Sty1 pathway regulates transcription of some genes that are relevant for the cAMP-PKA pathway (Stiefel et al, 2004;Davidson et al, 2004), implicating that there is a complex crosstalk between these pathways.…”
Section: Perspectivesmentioning
confidence: 99%